Determinants of well-being factors mediated by teacher commitment - Rahmatullah; Inanna; Rijal, Syamsu; Sahade; Aggarwal, Ashwani Kumar (Journal of Education and e-Learning Research, 2024)
The purpose of this study is to investigate the variables that affect students' academic well-being. This study found that individualized teaching, family support for learning and teacher dedication are some of the variables that have an impact on children's well-being. The study used a quantitative methodology with 57 students as the sample size. A questionnaire was used to collect the data and random sampling is used in the sampling process. Some of the data analysis methods used in PLS-SEM include path diagram models, validity tests, reliability tests, model fits, R squares and modified R squares, predictive relevance, collinearity, direct and indirect effects and hypothesis testing. The findings of the study demonstrate that well-being is significantly impacted by directly differentiated instruction that is customized to each student's needs and traits. The well-being of students is significantly impacted by parental learning support. Evaluation of the indirect effects reveals that the differentiated learning variable through teacher devotion significantly affects students' well-being. Parental support's indirect influence on the learning variable has a significant effect on children's wellbeing similar to how teacher dedication serves as a mediator. The research contribution to the development of literature is related to how the role of parent support in learning has led to increased teacher commitment. Effective implementation of individualized instruction and integration of parental assistance in learning into the learning process are accessible to teachers who have a strong dedication to their career. A committed teacher will create an inclusive learning environment that will ultimately realize the overall well-being of students.